All Days 2014
DOI: 10.2118/172215-ms
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Well Completion Designs to Meet Unique Reservoir and Production Requirements

Abstract: Well Completions design is continuously evolving to meet increasing requirements of down hole monitoring and control. The design of well completion has become more sophisticated as these requirements increase. Nowadays in the industry, it is rare to find a well completion that does not have some type of down hole sensor or inflow control. This paper presents overview of six different well completions designed to meet different reservoir and production requirements. Each of these design are integrations of exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…To build a more scientific and systematic governance framework for green and smart ports, this paper defines the development concept for green and smart ports and elaborates in six dimensions from the industry practice and academic research results, meaning greenness [28,29], agility [30,31], personalization [32][33][34], cooperation [35][36][37], intelligence [38,39], and liberalization [40,41] are the key elements for green and smart port development. The detailed introductions are shown in Table 1.…”
Section: Developing Concepts and Critical Factors Of Green And Smart Portsmentioning
confidence: 99%
See 1 more Smart Citation
“…To build a more scientific and systematic governance framework for green and smart ports, this paper defines the development concept for green and smart ports and elaborates in six dimensions from the industry practice and academic research results, meaning greenness [28,29], agility [30,31], personalization [32][33][34], cooperation [35][36][37], intelligence [38,39], and liberalization [40,41] are the key elements for green and smart port development. The detailed introductions are shown in Table 1.…”
Section: Developing Concepts and Critical Factors Of Green And Smart Portsmentioning
confidence: 99%
“…Greenness Industrial and production modes with high technology content, low resource consumption, and less environmental pollution [28,29] Agility Working methods guided by a quick and efficient methodology subject to constant reforms [24,31] Personalization New production models that are able to meet unique market requirements in the new market environment [32][33][34] Cooperation Strengthened international cooperation, enhanced port-city integration and increased cooperation with inland ports [35][36][37] Intelligence More modern intelligent technologies integrated into port working environments to improve port operation levels [38,39] Liberalization Relaxed government regulation to give full play to the role of market mechanism to facilitate trade [40,41] This paper considers 20 critical factors influencing the development of a green and smart port, referring to a comprehensive literature review as shown in Table 1. The greenness concept covers four factors: energy-saving and emission-reducing capability, pollution treatment capability, effective utilization of resources and environmental protection concept, and policy system.…”
Section: Dimension Descriptions Sourcementioning
confidence: 99%